Dasar Kerajaan Negeri Sabah Menangani Perkembangan Ajaran Sesat Dalam Islam - Asmady Idris; Shahril Yusof; Suraya Sintang; Issraq Ramli (2020)
The State of Sabah, through the State Religious Council, has legally ratified the fatwa (religious edict) upon 22 religious teachings which being classified as deviant and misrepresentative of Islam. The deviant teachings are considered to be incongruent with the central belief of Ahlus Sunnah wal-Jamaah as the fundamental basis of Islamic faith in Malaysia. Their religious dogmas are not only destabilising the solidarity of Muslim society, but also the security and the political stability of this country. In conjunction with this, the State Religious Fatwa Council, has taken firm action by gazetting the fatwa on all the 22 teaching groups as deviant and contradicting with the true principle of Islam. In order to analyse further the Sabah State policy in dealing with the development of deviant teachings, this study will divide the main focus of discussion into three focal issues. The first issue will discuss the conceptual deviant teachings phenomenon in a religious-faith community. The second issue will examine the scenario and the character of deviant teachings in Malaysia, particularly in Sabah. The third issue is to analyse State government policies based on the State Fatwa Enactment to curb the spread of deviant teachings among local Muslim community in Sabah. This is a qualitative study employs literature reviews and interviews with relevant respondents. The study findings have notified that Sabah has already a solid system which enable it to evaluate and classify one particular religious teaching whether it contradicts or not in accordance with Al-Quran, As-Sunnah and Ahlus Sunnah wal Jamaah doctrines. In curing and controlling the deviant teachings syndrome, the State Government has used different mechanisms including constant monitoring, conveying da’wah, and also setting up a rehabilitation centre in Sabah. The employment of this thorough approach is vital to ensure the spread of deviant teachings in Sabah is well taken care of.